Buprenorphine treatment and 12-step meeting attendance: Conflicts, compatibilities, and patient outcomes - Monico, Laura B. (J Subst Abuse Treat, 2015)
This analysis examines patient experiences and outcomes with 12-step recovery group attendance during buprenorphine maintenance treatment (BMT), two approaches with traditionally divergent philosophies regarding opioid medications for treatment of opioid use disorder. Using quantitative (n=300) and qualitative (n=20) data collected during a randomized trial of counseling services in buprenorphine treatment, this mixed-methods analysis of African Americans in BMT finds the number of NA meetings attended in the prior 6 months was associated with a higher rate of retention in BMT (p<.001) and heroin/cocaine abstinence at 6 month follow-up (p=.005). However, patients whose counselors required them to attend 12-step meetings did not have better outcomes than patients not required to attend such meetings. Qualitative narratives highlighted patients’ strategies for managing dissonant viewpoints on BMT and disclosing BMT status in community 12-step meetings. Twelve-step meeting attendance is associated with better outcomes for BMT patients over the first 6 months of treatment. However, there is no benefit to requiring meeting attendance as a condition of treatment, and clinicians should be aware of potential philosophical conflicts between 12-step and BMT approaches.